EVALUASI WAKTU DAN BIAYA PROYEK KONSTRUKSI MENGGUNAKAN PRECEDENCE DIAGRAM METHOD (PDM) DAN CRASHING - Muhammad Yuda Isyaracsa; Lioba Evita Anikusuma (STKIP Subang, 2026)
Construction projects require effective time management to minimize delays that can lead to increased costs and project completion delays. This study aims to analyze the time and cost evaluation of a two-story residential construction project using the Precedence Diagram Method (PDM) and Crashing to identify the critical path and determine the most efficient acceleration alternatives. This study uses the PDM method to construct a work network, identify the critical path, and calculate the project duration through forward pass, backward pass, and total float analyses. Subsequently, the Crashing method is applied by adding labor and overtime hours to evaluate time acceleration and changes in project costs. The analysis results show that the normal project duration is 37 weeks with the critical path A–B–C–D–E–F–H–I–M. Applying the Crashing method by increasing the workforce by 15% or adding overtime hours can accelerate the project duration to 33 weeks. However, the overtime option is more efficient because it achieves the same acceleration with a lower cost increase compared to increasing the workforce. Thus, the PDM method is effective in identifying the critical path, while the Crashing method using overtime is the most optimal acceleration alternative based on time and cost considerations.